3D Bioprinting of Pectin-Cellulose Nanofibers Multicomponent Bioinks - Pitton, Matteo; Fiorati, Andrea; Buscemi, Silvia; Melone, Lucio; Farè, Silvia; Contessi Negrini, Nicola (Frontiers in Bioengineering and Biotechnology, 2021)
Pectin has found extensive interest in biomedical applications, including wound dressing, drug delivery, and cancer targeting. However, the low viscosity of pectin solutions hinders their applications in 3D bioprinting. Here, we developed multicomponent bioinks prepared by combining pectin with TEMPO-oxidized cellulose nanofibers (TOCNFs) to optimize the inks printability while ensuring stability of the printed hydrogels and simultaneously print viable cell-laden inks. First, we screened several combinations of pectin (1, 1.5, 2, and 2.5% w/v) and TOCNFs (0, 0.5, 1, and 1.5% w/v) by testing their rheological properties and printability. Addition of TOCNFs allowed increasing the inks viscosity while maintaining shear thinning rheological response, and it allowed us identifying the optimal pectin concentration (2.5% w/v). We then selected the optimal TOCNFs concentration (1% w/v) by evaluating the viability of cells embedded in the ink and eventually optimized the writing speed to be used to print accurate 3D grid structures. Bioinks were prepared by embedding L929 fibroblast cells in the ink printed by optimized printing parameters. The printed scaffolds were stable in physiological-like environment and characterized by an elastic modulus of E = 1.8 ± 0.2 kPa. Cells loaded in the ink and printed were viable (cell viability > 80%) and their metabolic activity increased in time during the in vitro culture, showing the potential use of the developed bioinks for biofabrication and tissue engineering applications.